2010
DOI: 10.1177/1477153510376794
|View full text |Cite
|
Sign up to set email alerts
|

Field surveys of the effect of lamp spectrum on the perception of safety and comfort at night

Abstract: Public lighting improves visibility and provides orientation. It also contributes to the perception of comfort and safety of people outside after dark. At present, highpressure sodium lamps are widely used in street lighting. This is in part due to their high efficacy and relatively long lifetime (≥16 000 hours). Their use, however, comes at the expense of good colour rendering. Recently developed ceramic metal halide lamps provide many of the advantages of HPS in addition to white light and better rendering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 8 publications
1
100
0
2
Order By: Relevance
“…"Reassurance" describes the feeling of confidence a pedestrian might gain from road lighting (among other factors) to walk along a road, in particular if walking alone after dark, and is used here to encompass the terms "perceived safety" [Knight 2010] and "fear of crime" [Atkins and others 1991] as used in past studies. Reassurance is that which provides the comfort that makes someone feel less worried or less afraid or doubtful and restores confidence [Fotios, Unwin, and Farrall 2015].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Reassurance" describes the feeling of confidence a pedestrian might gain from road lighting (among other factors) to walk along a road, in particular if walking alone after dark, and is used here to encompass the terms "perceived safety" [Knight 2010] and "fear of crime" [Atkins and others 1991] as used in past studies. Reassurance is that which provides the comfort that makes someone feel less worried or less afraid or doubtful and restores confidence [Fotios, Unwin, and Farrall 2015].…”
Section: Introductionmentioning
confidence: 99%
“…For clarity, we acknowledge here that changes in lighting other than photopic illuminance may affect evaluations of reassurance, such as the spectral power distribution [Akashi and others 2004;Knight 2010] and spatial distribution of light [Haans and de Kort 2012]. We also acknowledge that lighting alone does not mediate reassurance but that it is affected also by physical features through evaluation of prospect and escape [Fisher and Nasar 1992], by factors of social psychology such as perceptions of attractivity and power, and expectations of evil intent [van der Wurff and others 1989] and that an effect of lighting may interact with these factors; for example, that a higher illuminance may have little effect in a location with a high level of entrapment (or low possibility for escape) [Blöbaum and Hunecke 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Darkness has a certain relationship with the occurrence of crime [1][2]. The crime prevention lighting aims at reducing crime occurrence through lighting design [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This result is diverse from other researches, for example: Fotios [9] stated that road lighting with white light provide safer feeling than yellowish light; while Knight [15] expressed that people perceive white light to be more comfortable and safer than the yellowish light; and Morante [11], reported that road lighting with white light provide higher perceived safety than yellowish light.…”
Section: Discussionmentioning
confidence: 61%